2015
DOI: 10.4067/s0717-95022015000100051
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in the Diagnosis of the Mental Nerve Loop: A Comparative Study Between Panoramic Radiography and Cone Beam Computed Tomography

Abstract: SUMMARY: Dental implant and chin osteotomy are executed on the mandible body and the mental nerve is an important anatomical limit. The aim of this research was to know the position of the mental nerve loop comparing result in panoramic radiography and cone beam computed tomography. We analyzed 94 hemimandibles and the patient sample comprised female and male subjects of ages ranging from 18 to 52 years (mean age, 35 years) selected randomly from the database of patients at the Division of Oral Radiology at Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
4
11
1
2
Order By: Relevance
“…Our results were indicative of considerable anatomical variability, as distances from the mental foramen reached up to 20 mm (2.0 cm). Couto-Filho et al, 26 evaluating only the anterior loop, obtained mesial measures of the mental foramen similar to those obtained this study. This variability could be related to the incisive canal, a structure not evaluated in the previous study by Couto-Filho et al 26 Due to these discrepancies, it is recommended that all surgical cases involving the anterior mandible be assessed individually rather than relying on averages.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our results were indicative of considerable anatomical variability, as distances from the mental foramen reached up to 20 mm (2.0 cm). Couto-Filho et al, 26 evaluating only the anterior loop, obtained mesial measures of the mental foramen similar to those obtained this study. This variability could be related to the incisive canal, a structure not evaluated in the previous study by Couto-Filho et al 26 Due to these discrepancies, it is recommended that all surgical cases involving the anterior mandible be assessed individually rather than relying on averages.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that the interpretation of 2-D images has limitations and often results in false negatives and false positives, as well as misestimating anterior loop extension. 2 3 22 26 The presence of the anterior loop was overestimated by as much as 40% in PAN images in a previous study, in which false positives were determined by dissection of the radiographed anatomical specimens. 2 Image overlapping and the degree of corticalization of the bony canals are factors that may affect the visualization of structures such as the anterior loop and incisive canal.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Studies have shown that panoramic radiography is not sufficient for presurgical implant planning in the mental region and may need to be supplemented with other modalities such as CT for better visualization of the area. [ 2 13 14 ] The CT and CBCT allow three-dimensional imaging without magnification and distortion. Of these, CBCT has the advantage of providing high-quality images with less radiation dose than CT.[ 4 7 10 ]…”
Section: Discussionmentioning
confidence: 99%